Extensive surgery in medication‐related osteonecrosis of the jaw for the prevention of infective endocarditis. Issue 2 (15th September 2021) - Narai, Takashi; Tamura, Takayuki; Fujii, Nobuyuki; Harada, Yusei; Watanabe, Soh; Kodani, Isamu
Abstract: Infective endocarditis (IE) is one of the most common diseases occurring in patients with valvular heart disease (VHD). One of the causes of IE is bacteremia caused by oral jaw infections, including medication‐related osteonecrosis of the jaw (MRONJ) and oral surgery. We performed an extensive surgery for MRONJ prior to aortic valve replacement with severe aortic stenosis (SAS) for IE prevention. In patients with SAS and MRONJ who are being suggested a surgery on standby for VHD, a prior extensive surgery for MRONJ should be considered to prevent the risk of IE.